Emotional Freedom Technique (EFT) dengan Metode Basic Recipe untuk Menurunkan Tekanan Darah - Nur Intan Hayati Husnul Khotimah; Randen Siti Jundiah; Imam Abidin; Haerul Imam; Aneu Restri Nur Aisah; Muhammad Alfi Anugrah Awaludin Ma’ruf; Rival Mulki Prasetia Nugraha (Universitas Faletehan, 2023)
Hypertension impacts on coronary artery blockage, infarction, heart failure, stroke, anxiety, and depression and cause of death; thus, a proper treatment must be done. One of the treatments is EFT therapy. This study aimed to analyze the effects of emotional freedom technique (EFT) therapy twice a week with the basic recipe method on lowering blood pressure. The design used in this study was a true experimental approach with a pre-posttest and control design. The sample of 50 people with hypertension was obtained by the consecutive sampling technique. They were divided 25-25 into the intervention and the control group. The data analysis used t-test. The results showed that the average systolic pressure before giving EFT therapy was 147.60 mmHg and the average diastolic pressure was 88.60 mmHg. Meanwhile, the average systolic pressure after giving EFT therapy was 136.20 mmHg and the average diastolic pressure was 76.24 mmHg. The blood pressure of the intervention group after EFT therapy showed a significant difference both in the systolic pressure (p value 0.020) and in the diastolic pressure (p value< 0.001). The analysis results showed that the blood pressures were lowered significantly after EFT therapy was given twice a week. EFT therapy is very useful for hypertensive patients as an alternative treatment to control their blood pressure.